Crush the cell how to defeat terrorism without terrorizing ourselves - Sheehan, Michael A. (Crown Publishers, 2008)
Offers a realistic study of what the United States needs to do to protect itself against terrorism, revealing why many of the current tactics are largely a waste and calling for a new approach that emphasizes the identification and destruction of terrorist cells.